The use of digitalization elements in teaching snowboarding to older preschool children - Bronnikov, S.A. (Theory and Practice of Physical Culture, 2026)
The article discusses the results of experimental work on the development and testing of a methodology for teaching older preschool children to snowboard using elements of digitalisation. Objective of the study is to develop and test a methodology for teaching snowboarding to older preschool children using digitalization elements. Methods and structure of the study. During the first lesson, the instructor showed children videos of adult and children’s competitions, a film demonstrating all technical elements, runs, and various riding styles, and presented information about snowboarding and its history using visual aids.